Students Questioning Skills in the Learning Process with Content Mastery Techniques at Islamic Boarding School - Nurfarida Deliani; Silfia Hanani; Kunalan Kuriaya; Hermawati Hermawati; Anggi Fitria; Elsy Pranita (AT-TA'LIM, 2023)
The positive impact of questioning skills is quite large on the learning process and student learning outcomes. Low questioning skills can cause students to hesitate when asking questions, thus forgetting the main idea of the question to be conveyed it affects effective learning in the classroom. The purpose of this study was to compare the difference in pretest scores before and post-test after participating in content mastery services. The research method used is quantitative using a Pre-Experiment design with One Group Pretest-Post-test Design. The subjects of this study were 36 students at Ponpes Perkampungan Minangkabau Padang. Determination of the subject of this study using a purposive sampling technique. The instrument used in this study was a self-assessing skill scale that had been tested for validity and reliability. The data analysis technique used is the Wilcoxon Signed Rank Test. The results of the data analysis stated that there was a significant difference in scores on the pretest and post-tests of students' questioning skills after participating in the content mastery service. Thus, content mastery services are effective in improving students' questioning skills.